Neonatal Gastrointestinal Perforations: A 7-year Experience in a Single Centre - Jain, Nitin; K Ratan, Simmi; Neogi, Sujoy; Shekhar Panda, Shasanka; Kumar, Chiranjiv; Kumar, Prafful (Journal of Neonatal Surgery, 2025)
Background: Neonatal gastrointestinal perforation presents important challenges to the management. It is is still a significant problem despite improved neonatal care and contributes to high mortality. The aim of this study was to present our experiences with, as well as the factors that affect the management and outcome of patients with neonatal gastrointestinal perforations. Material and Methods: Records of neonates with GIPs between February 2016 and August 2023 were retrospectively analyzed. Fifty-seven newborn cases that were operated on for gastrointestinal perforation in our hospital’s tertiary newborn intensive care unit were evaluated. The patients were divided into the two following groups: group 1, perforations related to necrotizing enterocolitis (NEC), and group 2, non-NEC perforations. Results: In total, 57 neonates (26 males, 31 females) participated in this study. The perforations were related to NEC in 18 patients (group 1; 31.6 %), and the other 39 patients (group 2; 68.4 %) were classified as non-NEC perforation cases. The incidence of neonatal GIP was 0.43 % in all newborn patients, while the incidence of perforation in NEC cases was 16 %. Of all patients, 36 (63.2 %) were premature. Non-NEC pathologies were the most common cause of GIP (68.4 %) and included gastric perforation (n = 3), band and segmental volvulus (n = 7), intestinal atresia (n = 4), esophageal atresia and tracheoesophageal fistula (n = 2), Hirschsprung’s disease (n = 14), appendicitis (n = 2), incarcerated inguinal hernia (n = 2), meconium peritonitis (n = 3) and idiopathic causes (n = 2). Primary surgical repair was performed in all cases without a conservative approach. The mortality rate related to GIP in newborn cases was 45.6 % (n = 26). The mortality rate in group 1 was 55.6 % (n = 10), as compared to group 2 (43.5 %, n = 17) (p < 0.05). In group 1, among the 10 newborn mortalities, 7 newborns had intestinal perforations (gastric and jejuno-ileal) while rest 3 newborns had colorectal perforations. Conclusion : GIPs are one of the most significant causes of mortality in newborns. The most common cause of perforations is non-NEC entities and can be seen in the entire intestinal system from the stomach to the colon. Surgical exploration is still the primary management